Cardiac remodeling and physical exercise: a brief review about concepts and adaptations - Cavalcante, P. A. M.; Perilhao, M. S.; da Silva, A. A.; Serra, A. J.; Junior, A. F.; Bocalini, D. S. (International Journal of Sports Science, 2016)
Training variable control, is relateed to frequency, duration, and intensity, that respond to the promoting changes in physical fitness. However, adaptations related to different exercise intensities are still controversial, both in regards to cardiovascular disorder prevention and rehabilitation. There are few studies dealing with cardiac adaptations under different exercise intensities, and that a better understanding physiological cardiac remodeling may inspire the design of a strategy to improve ventricular function in cardiac approach. Thus the objective of this review was to assess the influence of chronic aerobic exercise on cardiac adaptations, with a focus on different exercise intensities, as well as presenting a conceptual approach on cardiac remodeling process. Also was included the specific characteristics of cardiac remodeling in each cardiac adequacy step during training. New research trends were also outlined in order to guide studies into developing new therapy strategies for controlling cardiovascular diseases.